2014
DOI: 10.1111/pai.12266
|View full text |Cite
|
Sign up to set email alerts
|

Reintroduction failure after negative peanut challenges in children

Abstract: Reintroduction failure is a common problem in children after negative peanut challenge. To guide reintroduction and identify potential peanut-related symptoms at home, careful follow-up after negative DBPCFC is advised. When symptoms occur or persist, food challenge outcome needs to be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 18 publications
3
35
0
2
Order By: Relevance
“…Several studies have shown that 18% to 32% of patients do not introduce the food after passing an OFC 109, 110, 111. This is of concern as the recurrence of FA (particularly peanut) has been shown to occur if the food continues to be avoided after the OFC or is consumed in very small quantities 112, 113, 114.…”
Section: Clinical Reasoning To Diagnose Food Allergymentioning
confidence: 99%
“…Several studies have shown that 18% to 32% of patients do not introduce the food after passing an OFC 109, 110, 111. This is of concern as the recurrence of FA (particularly peanut) has been shown to occur if the food continues to be avoided after the OFC or is consumed in very small quantities 112, 113, 114.…”
Section: Clinical Reasoning To Diagnose Food Allergymentioning
confidence: 99%
“…3,4 Based on previous studies, approximately 25%-30% of previously allergic patients continue a food avoidance diet despite a negative challenge. 5,6 There are several factors that influence this rate of avoidance, most commonly food refusal, food-related symptoms, and fears of persistence of allergies. 5,6 We sought to assess the rate of food introduction after a negative OFC in our pediatric allergy population using an anonymous questionnaire.…”
Section: To the Editormentioning
confidence: 99%
“…5,6 There are several factors that influence this rate of avoidance, most commonly food refusal, food-related symptoms, and fears of persistence of allergies. 5,6 We sought to assess the rate of food introduction after a negative OFC in our pediatric allergy population using an anonymous questionnaire. Data collected included challenged food type, result of the OFC, the frequency of food introduction, and reasons for failure to incorporate the challenged food into the diet on a regular basis.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Toutefois, d'après les données de la littérature, au moins 25 % des enfants ayant toléré un TPO à l'arachide rapportent des symptômes plus ou moins importants lors de la réintroduction ultérieure de cet aliment à leur domicile, ou bien refusent cette réintroduction, par crainte d'une réaction allergique. van Erp et al ont suivi 103 enfants, explorés pour suspicion d'allergie à l'arachide mais qui avaient toléré le TPO effectué à l'hôpital, par des interviews téléphoniques réguliers, de façon à déterminer le pourcentage d'enfants poursuivant et tolérant la consommation d'arachide à domicile, et les causes et les facteurs potentiels de risque d'échec de cette réintroduction [52]. La réintroduction effectuée à domicile a été interrompue chez 33 enfants (32 %), pour l'essentiel suite à des réactions allergiques plus ou moins graves (33 % des cas), ou suite à un refus de l'enfant (45 %).…”
Section: Arachide Et Fruits à Coqueunclassified